1982
DOI: 10.1016/0005-2736(82)90413-8
|View full text |Cite
|
Sign up to set email alerts
|

Bilayers of phosphatidyldiacylglycerol and phosphatidylcholesterol give 31P-NMR spectra characteristic for hexagonal and isotropic phases

Abstract: Aqueous dispersions of phosphatidyidiacylglyceroi and phosphatidyicholesteroi are shown to form bilayers by differential scanning calorimetry, diphenylhexatriene fluorescence polarization, and electron microscopy; however, 3~ P-nuclear magnetic resonance spectra of these dispersions are characteristic of the 'hexagonal' and 'isotropic' phases, respectively. The theoretical relationship between the conformation of phospholipid molecules in bilayers and the shape of the 31 P-NMR line is examined. It is shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…This direct comparison of NMR and X-ray diffraction data shows that in our system, as in most cases described, 31P NMR line shape does correspond to a particular phospholipid conformation. Exceptions from this generalization have been predicted theoretically and by computer simulations (Thayer & Kohler, 1981;Banerjee et al, 1985) and have been reported experimentally (Hui et al, 1981;Noggle et al, 1982). Similar results as ours were observed on a somewhat different system (yeast PC) by Dawson et al (1984) where an isotropic 31P NMR peak was observed at 15-25 mol % DO at 25-37 °C, and the signal typical of the Hn phase appeared upon increase of the DO content to 33 mol %.…”
Section: Discussionsupporting
confidence: 90%
“…This direct comparison of NMR and X-ray diffraction data shows that in our system, as in most cases described, 31P NMR line shape does correspond to a particular phospholipid conformation. Exceptions from this generalization have been predicted theoretically and by computer simulations (Thayer & Kohler, 1981;Banerjee et al, 1985) and have been reported experimentally (Hui et al, 1981;Noggle et al, 1982). Similar results as ours were observed on a somewhat different system (yeast PC) by Dawson et al (1984) where an isotropic 31P NMR peak was observed at 15-25 mol % DO at 25-37 °C, and the signal typical of the Hn phase appeared upon increase of the DO content to 33 mol %.…”
Section: Discussionsupporting
confidence: 90%
“…The 31 P NMR resonance for hexagonal phases is markedly different from that found for a cubic or micellar phase, for which a narrow (fwhm ∼ 2 ppm) isotropic (symmetric) resonance would be expected. , Here however, the spectral line shape at 3 °C shows a deviation from an isotropic Lorentzian form. This sort of narrow, anisotropic spectrum lacking a well-resolved high-field shoulder observed at 3 °C has been previously observed in aqueous dispersions of diacylphosphatidylcholesterol and is believed to indicate the presence/formation of smaller structures (i.e., short hexagonal tubes), leading to additional motional averaging arising from particle tumbling and/or lateral diffusion of the lipids . Taken together, these results suggest that the structure of the fluid phase of the quaternary composition should be viewed as a hexagonal array of elongated/prolate structures, rather than of infinite cylinders.…”
Section: Resultssupporting
confidence: 71%
“…Such sharp peaks were described in several experiments in which glycophorin was chemically back inserted with other lipids (De Kruijff et al, 1991 ;Taraschi et al, 1982) and they were present in other systems in which peptides were inserted in lipids (Zidovetzki et al, 1988;Killian et al, 1990). Such sharp peaks are associated with high mobility of the polar head region in pure lipid systems but theoretical simulations showed that a small change in the orientation of the polar head caused a drastic modification in 31P-NMR anisotropy (Thayer and Kohler, 1981 ;Banerjee et al, 1985;Noggle et al, 1982). We previously described such a simulation by using the framework provided by others (Thayer and Kohler, 1981).…”
Section: Discussionmentioning
confidence: 86%